The Efek edukasi MPASI metode modifikasi terhadap pertumbuhan Bayi 6-7 bulan: Studi eksperimental di posyandu Kecamatan Karangtengah, Kabupaten Demak: Edukasi MPASI , Pertumbuhan bayi, Metode modifikasi - Ristya Widya Arumsari; Sri Priyantini; Hesty Wahyuningsih (Amerta Nutrition, 2023)
Background: Infant growth is defined as increased physical size or organ development. Such growth is usually monitored through anthropometric measurements. One of the factors that can affect infant growth is complementary feeding given by mothers. Objectives: This study aimed to determine the effect of education on complementary feeding using a modification method on the growth of infants aged 6-7 months at Integrated Health Centers (Posyandu) in Karangtengah, Demak Regency. Methods: This experimental study used a Pre- and Post-test control group design with samples of mothers and their infants aged 6-7 months. The intervention was given for three months as education on complementary feeding using a modification method, namely a combination of lectures, demonstrations, interactive discussions, practical sessions, and video presentations, as well as dissemination of information and consultation through a WhatsApp group. In addition, a group of mothers with awareness of complementary feeding was created, supervised by local volunteers and midwives during the healthcare services at posyandu. Results: The mean length increment for the intervention group (4.29 cm) was higher than that for the control group (2.63 cm) with p=0.000. Similarly, the mean weight increment for the intervention group (668.75 g) was also higher than that for the control group (344.00 g) with p=0.001. Conclusions: Education on complementary feeding using the modification method affected the growth of infants aged 6-7 months at Posyandu in Karangtengah, Demak Regency.